Multisensory stimulation modulates perceptual and post perceptual face representations: Evidence from event‐related potentials. (16th September 2018) - Estudillo, Alejandro J.; Kaufmann, Jürgen M.; Bindemann, Markus; Schweinberger, Stefan R.
Abstract: Seeing a face being touched in spatial and temporal synchrony with the own face produces a bias in self‐recognition, whereby the other face becomes more likely to be perceived as the self. The present study employed event‐related potentials to explore whether this enfacement effect reflects initial face encoding, enhanced distinctiveness of the enfaced face, modified self‐identity representations, or even later processing stages that are associated with the emotional processing of faces. Participants were stroked in synchrony or asynchrony with an unfamiliar face they observed on a monitor in front of them, in a situation approximating a mirror image. Subsequently, event‐related potentials were recorded during the presentation of (a) a previously synchronously stimulated face, (b) an asynchronously stimulated face, (c) observers' own face, (d) filler faces, and (e) a to‐be‐detected target face, which required a response. Observers reported a consistent enfacement illusion after synchronous stimulation. Importantly, the synchronously stimulated face elicited more prominent N170 and P200 responses than the asynchronously stimulated face. By contrast, similar N250 and P300 responses were observed in these conditions. These results suggest that enfacement modulates early neural correlates of face encoding and facial prototypicality, rather than identity self‐representations and associated emotional processes. Abstract : Multisensory stimulation with another face modulates event‐related potentials reflecting the perceptual processing of faces (N170) and perceived face distinctiveness (P200), but no later representations of facial identity (N250), or emotional responses (P300).